Review Article: Byzantium and the West: Perception and Reality (11th-15th C.), edited by Nikolaos G. Chryssis, Athina Kolia-Dermitzaki and Angeliki Papageorgiou, Abingdon and New York: Routledge, 2019 - COUREAS, Nicolaos (Byzantina Symmeikta, 2020)
Review Article:Byzantium and the West: Perception and Reality (11th-15th C.), edited by Nikolaos G. Chryssis, Athina Kolia-Dermitzaki and Angeliki Papageorgiou, Abingdon and New York: Routledge, 2019